15 000 ellipsoidal binary candidates in TESS: Orbital periods, binary fraction, and tertiary companions. Issue 1 (3rd April 2023) - Green, Matthew J; Maoz, Dan; Mazeh, Tsevi; Faigler, Simchon; Shahaf, Sahar; Gomel, Roy; El-Badry, Kareem; Rix, Hans-Walter
ABSTRACT: We present a homogeneously selected sample of 15 779 candidate binary systems with main sequence primary stars and orbital periods shorter than 5 d. The targets were selected from TESS full-frame image light curves on the basis of their tidally induced ellipsoidal modulation. Spectroscopic follow-up suggests a sample purity of 83 ± 13 per cent. Injection-recovery tests allow us to estimate our overall completeness as 28 ± 3 per cent with P orb < 3 d and to quantify our selection effects. 39 ± 4 per cent of our sample are contact binary systems, and we disentangle the period distributions of the contact and detached binaries. We derive the orbital period distribution of the main-sequence binary population at short orbital periods, finding a distribution continuous with the lognormal distribution previously found for solar-type stars at longer periods, but with a significant steepening at P orb ≲ 3 d, and a pile-up of contact binaries at P orb ≈ 0.4 d. Companions in the period range of 1–5 d are an order of magnitude more frequent around stars hotter than ≈ 6250 K (the Kraft break) when compared to cooler stars, suggesting that magnetic braking shortens the lifetime of cooler binary systems. However, the period distribution in the range 1–10 d is independent of temperature. We detect resolved tertiary companions to 9.0 ± 0.2 per cent of our binaries with a median separation of 3200 au. The frequency of tertiary companions rises to 29 ± 5 per cent among the systems with the shortest ellipsoidal periods. This large binary sample with quantified selection effects will be a powerful resource for future studies of detached and contact binary systems with P orb <5 d.